Pectin De-methylesterification and AGP Increase Promote Cell Wall Remodeling and Are Required During Somatic Embryogenesis of Quercus suber - Pérez-Pérez, Yolanda; Carneros, Elena; Berenguer, Eduardo; Solís, María-Teresa; Bárány, Ivett; Pintos, Beatriz; Gómez-Garay, Aránzazu; Risueño, María C.; Testillano, Pilar S. (Frontiers in Plant Science, 2019)
Somatic embryogenesis is a reliable system for in vitro plant regeneration, with biotechnological applications in trees, but the regulating mechanisms are largely unknown. Changes in cell wall mechanics controlled by methylesterification of pectins, mediated by pectin methylesterases (PMEs) and pectin methyl esterase inhibitors (PMEIs) underlie many developmental processes. Arabinogalactan proteins (AGPs) are highly glycosylated proteins located at the surface of plasma membranes, in cell walls, and in extracellular secretions, with key roles in a range of different processes. In this study, we have investigated changes in two cell wall components, pectins and AGPs, during somatic embryogenesis in Quercus suber, a forest tree of high economic and ecologic value. At early embryogenesis stages, cells of proembryogenic masses showed high levels of esterified pectins and expression of QsPME and QsPMEI genes encoding a PME and a putative PMEI respectively. At advanced stages, differentiating cells of heart, torpedo and cotyledonary embryos exhibited walls rich in de-esterified pectins, while QsPME gene expression and PME activity progressively increased. AGPs were detected in cell walls of proembryogenic masses and somatic embryos. QsLys-rich-AGP18, QsLys-rich-AGP17, and QsAGP16L1 gene expression increased with embryogenesis progression, as did the level of total AGPs, detected by dot blot with β-Glucosyl Yariv reagent. Immuno dot blot, immunofluorescence assays and confocal analysis using monoclonal antibodies to high- (JIM7, LM20) and low- (JIM5, LM19) methylesterified pectins, and to certain AGP epitopes (LM6, LM2) showed changes in the amount and distribution pattern of esterified/de-esterified pectins and AGP epitopes, that were associated with proliferation and differentiation and correlated with expression of the PME and AGP genes analyzed. Pharmacological treatments with catechin, an inhibitor of PME activity, and Yariv reagent, which blocks AGPs, impaired the progression of embryogenesis, with pectin de-esterification and an increase in AGP levels being necessary for embryo development. Findings indicate a role for pectins and AGPs during somatic embryogenesis of cork oak, promoting the cell wall remodeling during the process. They also provide new insights into the regulating mechanisms of somatic embryogenesis in woody species, for which information is still scarce, opening up new possibilities to improve in vitro embryo production in tree breeding.